The Bicentennial and governance: Constituent Assembly or constitutional reform? - Chiri Márquez, Renzo (2021)
In the framework of the recent general elections and in the context of the commemoration of the bicentennial of the Republic, there has been an intense legal and political debate among those in favor of moving towards a Constituent Assembly that fully renews the fundamental charter; and the defenders of introducing partial reforms to the current Constitution of 1993 through the mechanisms established therein for this purpose. This article explores the advantages, limitations and dangers of both routes. In the same way, it proposes a set of constitutional reforms always having as its objective the need to preserve the essential conditions for democratic governance and the strengthening of fundamental rights in Peru in the 21st century.